Growth and investigations of GaN-Ga2O3 nano-composites - Beh, K. P.; Yam, F. K.; Low, L. L.; Tneh, S. S.; Ng, Siow Woon; Tan, L. K.; Chai, Y. Q.; Hassan, Z. (Optoelectronics and Advanced Materials-Rapid Communications, 2012)
Gallium nitride (GaN) - gallium oxide (Ga2O3) nano-composites were synthesized through ammonolysis of Ga2O3 powder, with or without the addition of multi-wall carbon nanotubes (MWCNT). Both synthesized nano-composites having rod-shaped structure, while addition of MWCNT had resulted in hollow-like interior with some cavity walls. Vibrational measurement revealed that both samples contained mixture of GaN-Ga2O3, with GaN being the dominant. Optical measurements showed a high level of defects present in both samples. Violet-blue bands (VBL) were observed in both samples. Sample with added MWCNT exhibited blue shift relative to that of without MWCNT, which properties may governed by the contents of nitrogen.
CRIS-Team Scopus Importer:2022-11-02
Keywords: Carbon nanotubes; Composites; Gan; PL; Raman